TEKNIK KOMUNIKASI PRAMUWISATA LOKAL DALAM PROSES INTERPRETASI DESA WISATA HIJAU BILEBANTE - Zahira Athiya Ramadhani,; Jumraidin, Jumraidin; H. Lalu Ratmaja, (Juremi: Jurnal Riset Ekonomi, 2024)
This study aims to determine the communication techniques used by local tour guides in the Bilebante Green Tourism Village in the process of interpretation or storytelling to tourists. The method used is a qualitative method by conducting observations, interviews and documentation to several local tour guides in the Bilebante Green Tourism Village. The results of this study are that some tour guides communicate according to standards by self-taught and some have applied Onong Uchjana Effendy's communication techniques which include informative, persuasive, interaction / coercive and human relations communication techniques. Which in doing a communication is also very related to the elements of communication techniques, from Harold Laswell including; who (who / source), says what (what / message), in which channel (media), to whom (who / recipient), with what effect (impact / effect). So that some local guides in the Bilebante Green Tourism Village who have applied appropriate communication techniques have succeeded in attracting tourists to come back with the same personThis study aims to determine the communication techniques used by local tour guides in the Bilebante Green Tourism Village in the process of interpretation or storytelling to tourists. The method used is a qualitative method by conducting observations, interviews and documentation to several local tour guides in the Bilebante Green Tourism Village. The results of this study are that some tour guides communicate according to standards by self-taught and some have applied Onong Uchjana Effendy's communication techniques which include informative, persuasive, interaction / coercive and human relations communication techniques. Which in doing a communication is also very related to the elements of communication techniques, from Harold Laswell including; who (who / source), says what (what / message), in which channel (media), to whom (who / recipient), with what effect (impact / effect). So that some local guides in the Bilebante Green Tourism Village who have applied appropriate communication techniques have succeeded in attracting tourists to come back with the same person